iCPET Calculator: A Web‐Based Application to Standardize the Calculation of Alpha Distensibility in Patients With Pulmonary Arterial Hypertension - Jordan Elliott; Nainika Menakuru; Kellan Juliet Martin; Farbod Nicholas Rahaghi; Franz P. Rischard; Rebecca R. Vanderpool (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Pulmonary vascular distensibility associates with right ventricular function and clinical outcomes in patients with unexplained dyspnea and pulmonary hypertension. Alpha distensibility coefficient is determined from a nonlinear fit to multipoint pressure‐flow plots. Study aims were to (1) create and test a user‐friendly tool to standardize analysis of exercise hemodynamics including distensibility, and (2) investigate changes in distensibility following treatment in patients with pulmonary arterial hypertension. Methods and Results Participants with an exercise right heart catherization were retrospectively identified from the University of Arizona Pulmonary Hypertension (UA PH) registry and split into a pulmonary arterial hypertension group, a comparator group, and a control group. Right ventricular function was quantified using the coupling ratio and diastolic stiffness. Prototypes of the invasive cardiopulmonary exercise testing (iCPET) calculator were developed using Matlab, Python, and RShiny to analyze exercise hemodynamics and alpha distensibility coefficient, α (%/mm Hg) from multipoint pressure flow plots. Interclass correlation coefficients were calculated for interplatform and interobserver variability in alpha. No significant bias in the intraplatform (Matlab versus RShiny; intraclass correlation coefficient: 0.996) or interobserver (intraclass correlation coefficient: 0.982) comparison of alpha values. Afterload significantly decreased (P<0.05) with no change in alpha distensibility in the pulmonary arterial hypertension group at follow‐up. The comparator group had no change in pressure, resistance or alpha distensibility. There were no significant changes in RV diastolic stiffness at follow‐up. Conclusions The interactive user interface in the iCPET calculator allows exploration of alpha distensibility using standardized methods. No significant change in alpha distensibility at follow‐up suggests that alpha may be less modifiable in patients with long‐standing pulmonary arterial hypertension.